2012
DOI: 10.1001/jama.2012.7352
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Adjuvant Chemotherapy With Fluorouracil Plus Folinic Acid or Gemcitabine vs Observation on Survival in Patients With Resected Periampullary Adenocarcinoma

John P. Neoptolemos,
Malcolm J. Moore,
Trevor F. Cox
et al.

Abstract: ERIAMPULLARY CARCINOMAS arise from the head of the pancreas in the region of the ampulla of Vater and apart from pancreatic ductal adenocarcinoma comprise carcinomas of the bile duct, the ampulla itself, and the periampullary duodenum. 1,2 The incidence rates per 10 5 are 11.7 for pancreatic, 0.88 for bile duct, 0.49 for ampullary, and 0.01 for Author Affiliations are listed at the end of this article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
337
3
10

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 530 publications
(358 citation statements)
references
References 29 publications
(52 reference statements)
8
337
3
10
Order By: Relevance
“…For operable pancreatic cancers, the patients are usually treated with adjuvant chemoradiotherapy (Regine et al, 2008) in the United States and with chemotherapy (Neoptolemos et al, 2012) in Europe. Systematic therapy is the mainstay for metastatic pancreatic cancer (Tokh et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…For operable pancreatic cancers, the patients are usually treated with adjuvant chemoradiotherapy (Regine et al, 2008) in the United States and with chemotherapy (Neoptolemos et al, 2012) in Europe. Systematic therapy is the mainstay for metastatic pancreatic cancer (Tokh et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…However, IHCC, PHCC and DCC were grouped together in this study despite their obvious differences in anatomic location, etiopathogenesis, diagnosis, treatment and prognosis [6,11]. Furthermore, adjuvant therapy agents, doses and scheduling varied greatly among different literatures [12][13][14]. In addition, the clinical data of CCAs are usually collected over many years with a limited number of patients for the rarity of this disease, which inevitably lead to bias for the variability of diagnosis and treatment strategy.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the retrospective trials, which included limited sample sizes, heterogeneous patient populations and non-standardized therapies, suggested a marginal benefit of chemotherapy in reducing recurrence and an uncertain effect on survival (4,5). The only two prospective randomized controlled trials (RCT) currently available concluded that adjuvant chemotherapy did not improve survival (6,7).…”
Section: Introductionmentioning
confidence: 99%